Experimental Investigation of the Rutting Potential of Polymer-modified Asphalt Binders using the Multiple Stress Creep Recovery Test - Hoang, Tung; Nguyen, Van Bich (Engineering, Technology & Applied Science Research, 2025)
Polymer-modified binders have become increasingly important in enhancing the durability and strength of asphalt flexible pavements, allowing them to withstand higher traffic volumes, heavier loads, and extreme weather conditions. Although the Dynamic Shear Rheometer (DSR) test is widely used, it is inadequate to accurately capture the viscoelastic properties of polymer-modified asphalt binders. As a result, the Multiple Stress Creep Recovery (MSCR) test, a recently developed method for assessing the high-temperature performance of asphalt binders, is expected to replace the DSR for short-term aged binders. In this study, binders comprising 40/60 pen unmodified bitumen, a hard polymer-modified binder, and a softer polymer-modified binder, were evaluated using MSCR testing under various stress and temperature conditions. The MSCR results showed that incorporating Styrene–Butadiene–Styrene (SBS) modifiers into the bitumen significantly enhanced the permanent deformation resistance of the modified binders by reducing the non-recoverable compliance and increasing the recovery percentage. Moreover, a comparison of the MSCR results at the 3.2 kPa stress level with the AASHTO standard confirmed that the examined asphalt binders were modified with an elastomeric polymer of acceptable quality.